2006
DOI: 10.1149/1.2266454
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Laminated CeO[sub 2]–HfO[sub 2] High-k Gate Dielectrics Grown by Pulsed Laser Deposition

Abstract: The electrical and physical properties of CeO 2 -HfO 2 nanolaminates on Si͑100͒, by pulsed laser deposition, are investigated. Layers were deposited using pure CeO 2 and HfO 2 targets at various substrate temperatures ranging from 220 to 620°C at Ar + H 2 and O 2 and in situ postdeposition anneal of nanolaminates performed by controlled cooling from deposition temperature to room temperature under high oxygen pressure. After layer growth and anneal, top and bottom Au electrodes were deposited by sputtering. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Several oxide NL combinations such as Al 2 O 3 /TiO 2 , Al 2 O 3 /ZnO, ZrO 2 /HfO 2 , ZrO 2 /Gd 2 O 3 , HfO 2 /Ta 2 O 5 , CeO 2 /HfO 2 , HfO 2 /LaAlO 3 , Al 2 O 3 /ZrO 2 , Al 2 O 3 /MgO, , Al 2 O 3 /HfO 2 , , and so forth have been investigated to achieve improved electrical and dielectric properties required for aforementioned applications. Among these, the Al 2 O 3 /TiO 2 /Al 2 O 3 (ATA) NL has emerged as the most preferred candidate for high- k applications, owing to its low cost, excellent thermal stability, and superior electrical and dielectric properties. , Initial studies on ATA NLs with layer thicknesses of the order of a few nanometers have reported k values less than that of TiO 2 ; , however, significantly enhanced k values were achieved when thicknesses of Al 2 O 3 and TiO 2 layers were reduced to the subnanometric regime. Although dielectric constants of ∼1000 and 850 have been reported for atomic layer deposition (ALD)-grown ATA NLs with sublayer thicknesses ∼0.2 and 0.5 nm, these structures suffered from high dielectric losses of ∼10 and 2, respectively. , Furthermore, the observed high- k values for ATA NLs have been attributed to charge accumulation across the heterogeneous interfaces of insulating (Al 2 O 3 ) and semiconducting (TiO 2 ) sublayers due to the well-known Maxwell–Wagner (M–W) relaxation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several oxide NL combinations such as Al 2 O 3 /TiO 2 , Al 2 O 3 /ZnO, ZrO 2 /HfO 2 , ZrO 2 /Gd 2 O 3 , HfO 2 /Ta 2 O 5 , CeO 2 /HfO 2 , HfO 2 /LaAlO 3 , Al 2 O 3 /ZrO 2 , Al 2 O 3 /MgO, , Al 2 O 3 /HfO 2 , , and so forth have been investigated to achieve improved electrical and dielectric properties required for aforementioned applications. Among these, the Al 2 O 3 /TiO 2 /Al 2 O 3 (ATA) NL has emerged as the most preferred candidate for high- k applications, owing to its low cost, excellent thermal stability, and superior electrical and dielectric properties. , Initial studies on ATA NLs with layer thicknesses of the order of a few nanometers have reported k values less than that of TiO 2 ; , however, significantly enhanced k values were achieved when thicknesses of Al 2 O 3 and TiO 2 layers were reduced to the subnanometric regime. Although dielectric constants of ∼1000 and 850 have been reported for atomic layer deposition (ALD)-grown ATA NLs with sublayer thicknesses ∼0.2 and 0.5 nm, these structures suffered from high dielectric losses of ∼10 and 2, respectively. , Furthermore, the observed high- k values for ATA NLs have been attributed to charge accumulation across the heterogeneous interfaces of insulating (Al 2 O 3 ) and semiconducting (TiO 2 ) sublayers due to the well-known Maxwell–Wagner (M–W) relaxation .…”
Section: Introductionmentioning
confidence: 99%
“…7−9 Among these, multilayered NLs consisting of alternate ultrathin sublayers of two high-k dielectrics have recently garnered significant attention owing to their superior electrical and dielectric properties, suitable for a wide range of potential applications in next-generation data and energy storage devices, metal-oxide-semiconductor capacitors, and field-effect transistors. 10−13 Several oxide NL combinations such as Al 2 O 3 /TiO 2 , 14 Al 2 O 3 /ZnO, 15 ZrO 2 /HfO 2 , 16 ZrO 2 /Gd 2 O 3 , 17 HfO 2 /Ta 2 O 5 , 18 CeO 2 /HfO 2 , 19 HfO 2 /LaAlO 3 , 20 Al 2 O 3 /ZrO 2 , 21 Al 2 O 3 / MgO, 22,23 Al 2 O 3 /HfO 2 , 24,25 tigated to achieve improved electrical and dielectric properties required for aforementioned applications. Among these, the Al 2 O 3 /TiO 2 /Al 2 O 3 (ATA) NL has emerged as the most preferred candidate for high-k applications, owing to its low cost, excellent thermal stability, and superior electrical and dielectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…The film's structure and interface properties depend upon deposition processes. Several deposition techniques have been reported in literature for the preparation of CeO 2 films on Si for CMOS devices, including sputtering (Wang et al 2001), vacuum evaporation (Inoue et al 1990), MBE (Joumori et al 2004), PLD (Karakaya et al 2006), MOCVD (Ami and Suzuki 1998), and E-beam evaporation (Inoue et al 1999), etc. All these techniques require high temperature treatments which usually induces a deterioration of the device performance and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…However, the energy band-gap (E g ) of the HK dielectric and its conduction-band offset (ÁE C ) to the metal electrode become worse with increasing HK dielectric constant, 6) which can cause poor electrical performance, poor reliability, and thermal leakage current. In the literature, [7][8][9][10][11][12] zirconium oxide (ZrO 2 ) has emerged as one of the most promising HK dielectrics for MIM capacitors due to its outstanding characteristics including high dielectric constant, low leakage current, and high electrical performance. 13) However, there have been few reports on a MIM capacitor with single ZrO 2 layer, which would be necessary for high-density capacitors, although a stacked dielectric with ZrO 2 has been reported.…”
Section: Introductionmentioning
confidence: 99%